2020
DOI: 10.1007/s00508-020-01626-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical practice and placebo response: an inseparable bond?

Abstract: The history of medicine and the history of placebo are closely intertwined. To understand placebo and its effects this article gives a brief overview about its history, the possible mechanisms of action and its counterpart, nocebo. The Catholic Church used placebo around the sixteenth century for the separation from real and incorrect exorcisms, but it needed Henry Beecher during World War II to quantify the placebo effect as control arm in well-designed studies. Until today the different mechanisms of action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
1
0
3
Order By: Relevance
“…Other studies have suggested that finding may reflect methodological changes, such as an increased number of multicenter studies . Placebo effect has been shown to be associated with expectancy of active treatment and increased activity in reward circuitry . Industry-sponsored RCTs are often investigating novel agents, which may lead to increased expectations of efficacy by participants, although we are unable to confirm this possibility with available data.…”
Section: Discussionmentioning
confidence: 57%
“…Other studies have suggested that finding may reflect methodological changes, such as an increased number of multicenter studies . Placebo effect has been shown to be associated with expectancy of active treatment and increased activity in reward circuitry . Industry-sponsored RCTs are often investigating novel agents, which may lead to increased expectations of efficacy by participants, although we are unable to confirm this possibility with available data.…”
Section: Discussionmentioning
confidence: 57%
“…Сказанное позволяет предположить, что источников по истории плацебо, скорее всего, не так много. Но для последних лет пятнадцати спектр работ, целиком или частично посвященных истории плацебо, весьма разнообразен: не считая исследований из Великобритании и США, это австралийская [31], австрийская [32], бразильская [33], германские [21,34,35], израильские [36,37], испанская [38], итальянская [39], украинская [40], финская (монография) [41], французская [42], хорватская [43] и швейцарская [44] статьи. Обнаружены, как сказано выше, и шесть публикаций из России разной весомости [1,[23][24][25][26][27].…”
Section: источники по истории плацебо / Sources On the Placebo Historyunclassified
“…В трех источниках 2013-2020 гг. [32,34,41] назван врач Alexander Sutherland (родился перед 1730 г., умер после 1773 г. [34]; Великобритания) 21 .…”
Section: Review Articlesunclassified
See 1 more Smart Citation
“…Physical activity regularly improves the body's growth as well as development thus beneficially affecting social, psychological, mental as well as physical health which also contributes to learning [3]. Placebo & nocebo are also among the factors with their effects still waiting to be estimated and researched with placebo signifying positive beneficial effects [4]. Placebos, inactive substances, or processes that have no pharmacological impact, are becoming more and more popular in a variety of fields including clinical trials, where they are employed to assess the efficacy of various treatments [5].…”
Section: Introductionmentioning
confidence: 99%